A flexible optimization-based method for synthesizing intent-expressive robot arm motion. (September 2018) - Bodden, Christopher; Rakita, Daniel; Mutlu, Bilge; Gleicher, Michael
We present an approach to synthesize robot arm trajectories that effectively communicate the robot's intent to a human collaborator while achieving task goals. Our approach uses nonlinear constrained optimization to encode task requirements and desired motion properties. Our implementation allows for a wide range of constraints and objectives. We introduce a novel objective function to optimize robot arm motions for intent-expressiveness that works in a range of scenarios and robot arm types. Our formulation supports experimentation with different theories of how viewers interpret robot motion. Through a series of human-subject experiments on real and simulated robots, we demonstrate that our method leads to improved collaborative performance against other methods, including the current state of the art. These experiments also show how our perception heuristic can affect collaborative outcomes.